Nomadic firms in a globalizing economy: A comparative study - Frank R. Bruinsma; Cees Gorter; Peter Nijkamp (European Regional Science Association (ERSA), 1998)
The location patterns of modern firms appear to exhibit floating patternswith a tendency towards footlooseness. The spatial-economic dynamics - sometimes across teh border - of firms is encapsulated in the term 'nomadic firms'. This paper adresses the issue of nomadic behaviour of firms against the background of globalisation trends. After a critical discussion of globalisation phenomena and a review of the literature on nomadic entrepreneurial behaviour, the paper sets out t formaulate a series of relevant hypotheses of spatial relocation behaviour of international firms in a globalizing network economy. The analytical framework is tested by means of interviews among actual or potential nomadic firms, in both the Netherlands and abroad. Infrastructure quality and geographical accessibility appear to play an important role, but also opportunity seeking behaviour has a prominent place in nomadic behaviour. The comparitive study among the various firms located in various countries, which aims to identify the critical relocation factors, is based on principles of modern meta-analysis.
Keywords: 330